KREATIVITAS DALAM PEMIKIRAN CSIKSZENTMIHALYI - Aditya Ali (ArtComm, 2018)
Creativity is a term that has much to do with one's ability to create new ideas. This term was originally born in the world of psychology, because it is seen as part of human nature. But in its development, this term is actually widely used in the field of art and design. New phrases such as creative artists and creative designers emerge as a requirement for someone who wrestles the field. As a term inherent in art and design, a concept of a creative thinker has emerged as a humanistic psychologist, Csikszentmihalyi. The model and theory he developed was "Social Context of Creativity". That he thinks creativity is a system built from: person (individual), field (domain), and domain (community). According to Csikszentmihalyi these three things always exist, complement each other, build each other, and need each other in the creation of a creativity. Keywords: creativity, art and design, social context.